2012
DOI: 10.1111/jbi.12024
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the impact of Pliocene/Pleistocene sea level and climatic oscillations on the cladogenesis of the Cape legless skink, Acontias meleagris species complex, in South Africa

Abstract: Aim To determine the geographical boundaries among cryptic lineages and examine the evolutionary drivers of cladogenesis within the Cape legless skink, Acontias meleagris species complex.Location Coastal plains and adjacent interior of the Eastern, Northern and Western Cape provinces of South Africa.Methods A total of 231 specimens from 55 localities were collected from the entire known distribution range of the A. meleagris complex. Partial sequence data were collected from two mitochondrial DNA loci, 16S rRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 66 publications
(73 reference statements)
2
29
0
Order By: Relevance
“…The distribution of D.l.lutrix overlaps with several phylogeographic breaks for co-distributed lizard species (Fig. 1) (Daniels et al 2007; Engelbrecht et al 2013; Diedericks and Daniels 2014). A xeric biogeographic barrier known as the Bedford gap exists which separates the eastern and south-eastern part of the Cape Floristic Region (CFR) between East London and Port Elizabeth (Lawes 1990).…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…The distribution of D.l.lutrix overlaps with several phylogeographic breaks for co-distributed lizard species (Fig. 1) (Daniels et al 2007; Engelbrecht et al 2013; Diedericks and Daniels 2014). A xeric biogeographic barrier known as the Bedford gap exists which separates the eastern and south-eastern part of the Cape Floristic Region (CFR) between East London and Port Elizabeth (Lawes 1990).…”
Section: Introductionmentioning
confidence: 81%
“…Climatic oscillations are thought to be responsible for inducing dramatic impacts on the habitat and eco-physiological characteristics promoting cladogenesis (Hewitt 2000, 2004; Daniels et al 2007, 2009; Barlow et al 2013; Engelbrecht et al 2013). The effects of climatic impacts on terrestrial biota vary considerably depending on latitude, longitude, habitat and the topographic heterogeneity of the environment (Hewitt 2000, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have revealed concealed genetic divergence in multiple lineages of skinks from different regions of the world (Daniels et al, 2009; Engelbrecht et al, 2013; Heideman et al, 2011; Portik et al, 2011; Siler et al, 2011). The family exhibits a wide variety of ecomorphs, but the fossorial/semi-fossorial forms typically have reduced vagility that can facilitate population fragmentation and divergence by historical climatic and geographic processes.…”
Section: Introductionmentioning
confidence: 99%
“…Evolutionary inferences derived from DNA sequences [particularly the mitochondrial cytochrome c oxidase subunit 1 ( COI ) data and to a lesser extent nuclear loci] are widely used to describe alpha diversity and identify cryptic species, and have gained recent momentum (albeit with considerable criticism) due to the advocacy of the “Barcoding of Life” initiative (Hebert et al., ,b, ,b; de Salle et al., ; Hickerson et al., ). Cryptic speciation has been discovered in several eumetazoan lineages (Hedin and Wood, ; Baker et al., ; Boyer et al., ; Daniels et al., ; Daniels, , ; McDonald and Daniels, ; Engelbrecht et al., ; FernĂĄndez and Giribet, ; Medina et al., ). Molecular systematic studies of cryptic species have revealed substantial hidden diversity and localized endemism, negating the traditional paradigm of species with cosmopolitan distributions and forcing a rethink of units for conservation priority (Bickford et al., ).…”
mentioning
confidence: 99%